Cultural Dimensions and Their Influence on Entrepreneurial Decision-Making: A Cross-Cultural Analysis - Hamdan; Adiyanto, Yoga; Sunaryo, Deni; Auroh, Yusrotul; Hickmatullah, Iman (Yayasan Sinergi Kawula Muda, 2025)
This study investigates the nuanced influence of cultural factors on entrepreneurial behavior in the global business landscape, specifically examining how cultural dimensions shape decision-making processes and overall business strategies. Utilizing a mixed-methods approach that combines in-depth interviews and quantitative surveys across diverse cultural contexts, the research uncovers how dimensions such as individualism-collectivism and tolerance for uncertainty directly impact entrepreneurial practices. Key findings demonstrate that cultural values significantly modulate entrepreneurial behavior in critical domains, revealing that individualistic cultures tend to foster more independent and risk-taking decision-making, while collectivistic cultures prioritize consensus and group harmony. Additionally, the study shows that cultural orientation towards long-term or short-term perspectives substantially shapes innovation approaches, with long-term-oriented cultures more likely to invest in sustainable innovation. Furthermore, the research indicates that cultural tolerance for uncertainty correlates directly with entrepreneurs' willingness to experiment and adapt in volatile market environments. These insights provide valuable implications for entrepreneurs and policymakers, emphasizing the importance of culturally sensitive business strategies. By understanding how cultural factors systematically influence entrepreneurial behavior, organizations can develop more nuanced and context-specific approaches to international business development. Ultimately, this research contributes to a deeper understanding of how cultural contexts fundamentally shape entrepreneurial opportunities and challenges in today's interconnected global economy.